Assessment of compliance of prohibition of smoking (under section-4 of cigarettes and other tobacco products act) in Raipur city (C.G.), India: a cross sectional study - Kummar, Jitendra Kumar; Jain, Kamlesh; Verma, Nirmal; Sinha, Ashish; Bhawnani, Dhiraj; Prashad, Manish (International Journal Of Community Medicine And Public Health, 2018)
Background: Use of tobacco has been proven to be one of the leading causes of preventable premature deaths and diseases across the globe. The global adult tobacco survey (GATS) India report 2009-10 estimates 34.6% of India’s adult population use tobacco in some form or other. The government of India has taken various initiatives for tobacco control by enacting comprehensive tobacco control legislation (Cigarette and Other Tobacco Products Act COTPA, 2003). The objective of the study was to assess the level of compliance of section 4 of COTPA in public places of Raipur. Methods: A cross sectional observational study was conducted in Raipur. The study was done around 480 public places for observing the compliance of section 4 of COTPA. Results: From the total 480 public places visited, 36.9% public places displayed “No Smoking” signage, out of 117 public places where “No Smoking” signage displayed only 11.3% were as per the COTPA specification. Only 12.3% of public places active smoking was observed during visit. Conclusions: This finding suggests a poor level of compliance of section 4 of COTPA in Raipur. Although the law has been drafted comprehensively, it is implemented only to certain extent.